2019
DOI: 10.1097/inf.0000000000002047
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Syndecan-1 in Patients With Kawasaki Disease

Abstract: SDC-1 serum levels may mirror vascular endothelial damage and inflammation in KD. This might be utilized as a potential novel target for coronary artery protection in KD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…Anemia is a common clinical feature in KD patients [31]. In the current study, anemia was more common in the atypical patients than in the typical group.…”
Section: Discussionsupporting
confidence: 46%
“…Anemia is a common clinical feature in KD patients [31]. In the current study, anemia was more common in the atypical patients than in the typical group.…”
Section: Discussionsupporting
confidence: 46%
“…Similar to our COVID-19 case patient, elevated resistin is found in plasma from KD patients (17,18). Post-IVIg therapy, 3-5 days, plasma resistin levels in KD patients significantly decreased (12).…”
Section: Discussionsupporting
confidence: 85%
“…It has been shown that in the acute phase of Kawasaki disease, circulating levels of VEGLX (syndecan-1 and hyaluronic acid) are significantly elevated, and serum hyaluronic acid is the most useful prognostic biomarker for predicting future onset or exacerbation of coronary artery lesions in Kawasaki disease [ 46 ]. Serum levels of soluble syndecan-1, one of the major core proteins expressed in the VEGLX, are thought to reflect vascular endothelial damage and inflammation in Kawasaki disease [ 81 ]. Considering the common pathogenesis of Kawasaki disease and COVID-19, VEGLX damage has been suggested to be a biomarker in Kawasaki disease, and glycocalyx-associated biomarkers will likely contribute to the early detection of severe cases of COVID-19 in children and young adults, whose incidence of the disease is rare, but are prone to severe illnesses once they develop.…”
Section: Kawasaki Disease Shock Syndrome and Veglxmentioning
confidence: 99%